AIMS OF TEACHING FOREIGN LANGUAGES - Z.X.Bannopova; Mukhlisa Egamberdiyeva Shuhratovna (TADQIQOTLAR.UZ, 2024)
Abstract: In today's rapidly developing era, learning foreign languages is like having two different keys to the same door. Also, teaching foreign languages through effective methods is also important. The goals of foreign language education are the cause of wide discussions in the methodological literature. In the sixties of the last century, the terms of practical educational and educational goals were interpreted in accordance with the requirements of the time. This article is about the main goals and tasks of teaching foreign languages.